Pemberdayaan Usaha Melalui Modal Sosial di Kabupaten Pamekasan - Mujaddidi, Ah. Shibgahtullah Mujaddidi (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2023)
Social capital is human resources in having a social network. The term social capital refers to the capacity of the individual to obtain something of value as well as a symbol of social relations to group membership. This form of social capital arises from individual, family, group, and community relationships that are accesses that derive valuable profits from resources. Based on this, there are two discussions that are the focus of this study, namely: First, How social capital in the Aisyah batik ecoprint business fostered by MCI Pamekasan; Second, How to apply social capital in the empowerment of Aisyah Batik Ekoprint business. This research uses descriptive methods or analysis using a qualitative approach. From this study, the author can conclude that the application of social capital in the Aisyah Batik Ecoprint business applies to three points in the concept of social capital, namely: Network, Trus / Trust, Norms / Values. Where the network here is like Aisyah using existing relationships such as friends, relatives, neighbors, and also using tools such as social media. Then what is given to volunteers is in the form of trust in the process of making motiv ecoprint itself and trust given to buyers in the form of friendly service, delivery according to what is ordered and on time in the delivery of goods. The norms/values here are felt by the volunteers from the generosity of Aisyah which is very well given to her and is also felt for buyers in terms of the quality of the goods they buy.